On the Rate Sensitivity of Coal - Klepaczko, J.R. (Engineering Transactions, 1983)
This рареr describes the development of quasi-static and dynamic techniques applicable to compression testing of coal over a strain rate range of (…). At low and moderate strain rates a closed loop machine was used, while at high strain rate was accomplished with a newly-developed Hopkinson pressure bar apparatus. The loading direction was perpendicular to the specimen bedding plane (Z-direction) of all of the tests. Test results show a strong dependence of ultimate or crushing strength on the rate of deformation for the high region (…), whereas at low and intermediate strain rates the strength values seem to be rate insensitive.